2023
DOI: 10.1002/jmv.28713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical manifestations in mpox patients living with HIV versus without HIV: A systematic review and meta‐analysis

Abstract: Currently, many cases of mpox patients living with the human immunodeficiency virus (HIV) have been reported. Immunocompromised mpox patients, including those living with HIV are noted for an increased risk for severe symptoms; however, existing studies did not focus on the statistical comparison of mpox outcomes associated with HIV. Thus, we conducted a systematic review and meta-analysis to evaluate and compare the clinical manifestations of mpox in people living with HIV (PLWH) and people without HIV. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 115 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…In our study the percentage of patients coinfected with HIV was compared to other cohorts and amounted to 45.7% 11–13 . Higher prevalence of rectal signs and symptoms among PWH is now reported in the literature 14,18,30,33 . This phenomenon did not vary by HIV immune status and most likely explanation is related to the exposure site.…”
Section: Discussionmentioning
confidence: 53%
“…In our study the percentage of patients coinfected with HIV was compared to other cohorts and amounted to 45.7% 11–13 . Higher prevalence of rectal signs and symptoms among PWH is now reported in the literature 14,18,30,33 . This phenomenon did not vary by HIV immune status and most likely explanation is related to the exposure site.…”
Section: Discussionmentioning
confidence: 53%
“…Global mpox outbreak has shed light on sexual activity and mpox transmission being strongly associated 11 . A link between specific sexual practices and lesions location, with frequently risky sexual behaviours was evident in mpox cases 11,89,90 . Further, MPXV isolated from infectious sexual fluids and anogenital lesions were often observed before the obvious symptoms appear, supporting the theory of direct inoculation during active sex.…”
Section: Mpox Hiv and Std Co‐infection Risksmentioning
confidence: 78%
“…88 The risk of severe mpox among the subjects living with HIV patients was ever higher as compared to the ones without HIV. 89 Clinical manifestations of mpox in the subjects with and without HIV in 99 studies covering 2413 patients from 27 countries were meta-analysed, and it was found that skin rash, proctitis, cough and diarrhoea differently manifested between the groups. Secondary infections in smallpox unvaccinated MPXV contacts increased by 10% with 1%-11% CFR.…”
Section: Mpox Hiv and Std Co-infection Risksmentioning
confidence: 99%
See 2 more Smart Citations